Electronic structure and number theory : bohr's boldest dream - Comba, Peter; Boeyens, Jan C.A (Structure and Bonding, 2013)
J.C.A. Boeyens and P. Comba             Chemistry by Number Theory J.C.A. Boeyens                                   Chemistry in Four Dimensions C.J.H. Schutte                        Is the Rydberg-Ritz relationship valid? J.C.A. Boeyens                             Calculation of Atomic Structure     J.C.A. Boeyens                                                 Covalent Interaction P. Comba and J.C.A. Boeyens                                Molecular Shape J.C.A. Boeyens and D. C. Levendis                             All is Number